Urgensi Profesionalisme Guru di Pendidikan Sekolah Dasar - Nasution, Hamni Fadlilah (AR-RIAYAH : Jurnal Pendidikan Dasar, 2017)
The low quality of education in Indonesia can also be known from the Human Development Report, which states that the Human Development Index for 2004 Indonesia position is ranked 111th out of 177 countries surveyed. Teachers play an important role in the progress of education quality. Professional teachers are teachers who are able to master and control changes with science and technology insights. Professional teachers are teachers who are able to run the competencies they have. Four components of the competency standards that teachers must possess are: Personality competence, Pedagogic competence, Professional competence and social competence. The development of professionalism of elementary school teachers can also be pursued through a system called educational supervision, certification, with a professional teacher coaching system (SPP-Teacher) and learning tasks. The coaching program is useful to improve the quality of teachers so that a positive impact on the success of education